Investigation of Electrical Treeing in Perspex Material - Alzoubi, Mohammad Abderrazzaq (Technium Electro, 2024)
Perspex material, does not only belong to a big family of polymers, but it is also used for large number of electrical and non-electrical applications. This paper investigates the aging mechanism of Perspex material under high electric field. Electrical treeing phenomenon is studied using Perspex samples with electrodes of a pin-to-plane configuration. The growth of electrical tree in Perspex is measured and analyzed with the aid of an advanced microscope, equipped with a high resolution camera and connected to a personal computer. A number of distinct stages are assigned to characterize the electrical tree development. The area occupied by the tree channels is calculated using equal-area squares. This approach is employed to measure the growth rate of electrical trees under dry and wet conditions. Finally, the tree construction, shape and growth speed are studied and analyzed to distinguish between treeing phenomenon under wet and dry conditions of fabricated Perspex specimens.